Nonfarm Participation and Household Educational Investment: Evidence in Rural Indonesia - Dian Fitriana Arthati; Rus'an Nasrudin (Jurnal Ekonomi Pembangunan, 2025)
Participating in nonfarm employment as a diversification strategy increases the probability of farm households becoming less vulnerable to income shocks and improves rural household welfare. This study aims to fill the research gap about the impact of nonfarm participation on rural household educational investment using nationally representative data for Indonesia. Using topographical characteristics in each district as the instrumental variable (IV). This study reveals that participating in nonfarm employment significantly contributes to enhancing household educational expenditure in rural farming households. The OLS specification without controls yields a negative and insignificant coefficient for nonfarm participation. With household and district controls, the estimate becomes positive but remains small at 0.11 percentage points. The IV estimate is larger at 3.39 percentage points, indicating possible downward bias in the OLS results, likely related to unobserved factors that jointly affect nonfarm participation and educational spending with negative bias. There is substantial heterogeneity in the impacts of nonfarm participation across subsamples. The role of nonfarming is relatively higher in male-headed households and in households that run their own farm business assisted by temporary or unpaid workers. Nonfarm employment plays an essential role and is more prominent in eastern Indonesia. Income diversification to nonfarm sectors can potentially increase educational investment, particularly in relatively lagging regions, thereby reducing inequality in rural education.